Thinking about criminal justice in Canada - O'Regan, Karla (Emond, 2017)
"Drawing on well-known case studies to connect the book's theoretical content to real world issues, it lays out the key concepts, terms, and history for readers before shifting its focus to an exploration of key questions and issues in Canadian criminal justice today."--